2019
DOI: 10.1002/adtp.201900143
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite Polymer Scaffolds Responding under External Stimuli for Drug Delivery and Tissue Engineering Applications

Abstract: The blossoming development of nanomaterials and polymer science has opened the way toward new biocompatible scaffolds responding remotely to external stimuli (magnetic field, light, electric field). Such smart scaffolds are envisioned as new implantable tissues displaying multiple therapeutic and imaging functionalities. They hold great promises to achieve a controlled delivery of therapeutics for various diseases, or to ensure a stimuli‐induced cellular response for bone, cardiac, or muscle tissue engineering. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 252 publications
0
21
0
Order By: Relevance
“…For instance, photothermal nanoparticles (i.e., metal‐based, carbon nanotubes, graphene oxide, or polydopamine) can act as transducers capable of convert incoming light inputs to locally dissipated heat. [ 131,135 ] As a result, through the combined action of photoabsorbing nanomaterials interconnected to thermo‐responsive components, systems that previously responded only to temperature changes can be easily transformed into light‐responsive hybrid platforms. Also, these features are particularly advantageous as they allow the use of low energy NIR light with vastly improved tissue penetration depth compared to UV light.…”
Section: Stimuli‐responsive Nanocomposite Hydrogels and Biomedical Apmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, photothermal nanoparticles (i.e., metal‐based, carbon nanotubes, graphene oxide, or polydopamine) can act as transducers capable of convert incoming light inputs to locally dissipated heat. [ 131,135 ] As a result, through the combined action of photoabsorbing nanomaterials interconnected to thermo‐responsive components, systems that previously responded only to temperature changes can be easily transformed into light‐responsive hybrid platforms. Also, these features are particularly advantageous as they allow the use of low energy NIR light with vastly improved tissue penetration depth compared to UV light.…”
Section: Stimuli‐responsive Nanocomposite Hydrogels and Biomedical Apmentioning
confidence: 99%
“…[ 158,167 ] Akin to incorporating photothermal nanoparticles within thermally‐sensitive biomaterials, integrating magnetic nanoparticles with thermo‐responsive hydrogel networks allows for manipulation of assembly/disassembly states through external magnetic stimulation, thus providing opportunities for attaining on‐demand pulsatile drug release as well as tailoring shape memory architectural designs. [ 135,168,169 ] For instance, SPION‐loaded poly(N‐isopropylacrylamide)‐based hydrogels exposed to alternating magnetic fields demonstrated control in real‐time over their swelling behavior as well as pulsatile release of model drug pyrocatechol violet, owing to the reversible network collapse/expansion in response to remote controlled cyclic heating. [ 170 ] Although highly promising, these platforms typically display brittle networks with poor mechanical properties, and could benefit from mechanical strengthening in the foreseeable future.…”
Section: Stimuli‐responsive Nanocomposite Hydrogels and Biomedical Apmentioning
confidence: 99%
“…The design of composite membranes allowing the precise control of the release kinetics of drugs emerged this last decade for advanced applications in wound dressing, tissue engineering and nanomedicine. [1,2] Especially, in the case of hydrophilic drugs, the controlled delivery over time is an important issue which has to be taken into account in order to deliver the optimal amount of therapeutics to a targeted diseased area while avoiding burst release and undesirable side effects due to overdose.…”
Section: Introductionmentioning
confidence: 99%
“…The elaboration of mats with an organized arrangement of the nanofibers finds a wide range of applications. Among them, one can cite biomimetic scaffolds for tissue engineering applications, [ 42 ] drug delivery devices, [ 43 ] smart scaffolds responding under external stimuli, [ 44 ] advanced nanofibrous materials for fuel cells and batteries [ 45 ] or even hierarchical structure for catalytic applications. [ 46 ] The online measurement of the surface potential during electrospinning is therefore an efficient tool allowing the control of 2D and even 3D fiber structuration when micropatterned collectors are used for such targeted applications.…”
Section: Resultsmentioning
confidence: 99%
“…The microparticles can bring to these materials dedicated functionalities such as controlled drug delivery [48] or magnetic or photonic stimuli responsivity for advanced nanomedicine treatments. [44] As in the case of composites made of several types of nanofibers, the online measurement of the surface potential could allow the control of the mat's composition throughout its thickness, a key parameter for the fine tuning of the drug release kinetic. [48,49] It has been also demonstrated that the simultaneous electrospraying of microparticles during electrospinning nanofibers allows the fabrication of 3D structured composite when a micropatterned collector made of regularly distributed protuberances is used.…”
Section: Surface Potential In the Case Of A Micropatterned Collectormentioning
confidence: 99%